1987
DOI: 10.1007/bf01253599
|View full text |Cite
|
Sign up to set email alerts
|

Activation of striatal neurons by dexamphetamine is antagonized by degeneration of striatal dopaminergic terminals

Abstract: Unilateral degeneration of nigrostriatal dopaminergic terminals by the intranigral infusion of 6-OHDA produced a decrease in spontaneous multiple unit activity (MUA) in both the ipsilateral and contralateral striata of freely moving rats. Nigral lesions also attenuated the dexamphetamine-induced increase in MUA in the ipsilateral but not in the contralateral striatum. The magnitude of the attenuation in the ipsilateral striatum was directly proportional to the percent depletion of dopamine. Similarly degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 44 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…This increase was attributed by the authors to a compensatory mechanism occurring in the intact hemisphere that contributes to regenerative processes following nigrostriatal dopaminergic denervation (Nikolaus et al, 2003). Other evidences supporting the compensatory capacity of the contralateral striatum are not limited to imaging findings: increased levels of extracellular DA in striatal dialysates or postmortem striatum contralateral to 6-OHDA lesion (Robinson and Whishaw, 1988;Warenycia and McKenzie, 1987) were described decades ago. Another compensatory response from the intact hemisphere described in the unilateral 6-OHDA model is a long-term increase in dendritic arborization in the motor cortex contralateral to the lesion, whereas no changes were observed in the ipsilateral cortex (Miklyaeva et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…This increase was attributed by the authors to a compensatory mechanism occurring in the intact hemisphere that contributes to regenerative processes following nigrostriatal dopaminergic denervation (Nikolaus et al, 2003). Other evidences supporting the compensatory capacity of the contralateral striatum are not limited to imaging findings: increased levels of extracellular DA in striatal dialysates or postmortem striatum contralateral to 6-OHDA lesion (Robinson and Whishaw, 1988;Warenycia and McKenzie, 1987) were described decades ago. Another compensatory response from the intact hemisphere described in the unilateral 6-OHDA model is a long-term increase in dendritic arborization in the motor cortex contralateral to the lesion, whereas no changes were observed in the ipsilateral cortex (Miklyaeva et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…The finding of increased levels of extracellular dopamine in striatal dialysates contralateral to 6-OHDA (Robinson and Whishaw, 1988), which until the present study has not had a potential behavioral correlate, coupled with more recent evidence of bilateral upregulation of D2 receptor density following unilateral 6-OHDA lesions (Ferre and Fuxe, 1992;Nikolaus et al, 2003;Waszczak et al, 2006) suggest that the "intact" striatum may have the capacity for increased dopaminergic signaling, possibly via the D2 pathway. Evidence also exists showing an upregulation in post-mortem striatal dopamine content (as measured by HPLC) in striata contralateral to a severe 6-OHDA lesion relative to the striata of sham-operated controls (Warenycia and McKenzie, 1987), though this is not consistently found. Finally, bilateral electrophysiological anomalies have been observed in the striatum, substantia nigra, and subthalamic nucleus of animals following unilateral 6-OHDA infusions (Warenycia and McKenzie, 1987;Breit et al, 2006;White-Cipriano and Waszczak, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also exists showing an upregulation in post-mortem striatal dopamine content (as measured by HPLC) in striata contralateral to a severe 6-OHDA lesion relative to the striata of sham-operated controls (Warenycia and McKenzie, 1987), though this is not consistently found. Finally, bilateral electrophysiological anomalies have been observed in the striatum, substantia nigra, and subthalamic nucleus of animals following unilateral 6-OHDA infusions (Warenycia and McKenzie, 1987;Breit et al, 2006;White-Cipriano and Waszczak, 2006). In this paper we found that systemic administration of the dopamine antagonist haloperidol did lead to a deficit in the PIT test, indicating that although nondopaminergic changes might be responsible for enhanced reactivity on the unimpaired side following unilateral 6-OHDA lesion, intact dopamine systems are nevertheless important for normal execution of this task.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of corticostriatal excitatory input to the phasic episodes of action potential firing can be estimated from the effect of removing the cortex. Bilateral removal of the fronto-parietal cortex has been shown to decrease the neural activity recorded from units in the neostriatum of behaving rats (Warenycia and McKenzie, 1987). Burst firing is less frequent and less intense in the putamen after lesions of cortical areas 4 and 6, which project to it (Aldridge and Gilman, 1991).…”
Section: Corticostriatal Afferentsmentioning
confidence: 99%